Оцінка сучасного стану окремих компонентів агроландшафтів Житомирщини - Каленська, О.В. (Економіка природокористування і охорони довкілля, 2013)
Розглянуто питання функціонування агроландшафтів в Україні як нового об’єкта господарювання агропромислового комплексу, оптимального способу використання ресурсів агроландшафтів та їх охорони. Визначено проблеми, пов’язані з прискореним падінням родючості ґрунтів, а саме: зменшується вміст і погіршується якість гумусу, посилюються процеси ерозії, вторинного засолення й осолонцювання, збільшуються ареали техногенно забруднених і порушених ґрунтів. The article is devoted to the functioning landscapes in Ukraine as a new object management agribusiness complex, the best way to use resources, agricultural landscapes, protection of landscapes. State Land Resources of Ukraine is a growing concern due to the rapid decline of soil fertility: content decreases and the deteriorating quality of humus, aggravated erosion, salinization and alkalinization, growing areas polluted and disturbed soils. These and other destructive processes destroy not only the soil but also the entire landscape area of Ukraine. There is a rapid transformation of our prosperous land in the Badlands. The reason is the lack of ecological imperative of human activity in everyday life and in the workplace. And if any attempt were made to protect the environment, it was (and is) a non-system of so-called "fight" separately with each of the degradation processes without the necessary consideration of all components of the processes and phenomena that occur in landscapes.